A Visit with Dr. Louis Woolf, Recognizing His 100th Birthday and His Contributions to the Diagnosis and Treatment of Phenylketonuria - R. Rodney Howell; Graham Sinclair (International Journal of Neonatal Screening, 2020)
One of the most dramatic discoveries in metabolic disease research was that of Ashbørn Følling, who in 1934, published his research outlining unusual biochemical findings in a set of siblings with severe developmental delay [...]